2017
DOI: 10.1589/jpts.29.1612
|View full text |Cite
|
Sign up to set email alerts
|

The impact of closed versus open kinetic chain exercises on osteoporotic femur neck and risk of fall in postmenopausal women

Abstract: [Purpose] This study aimed to investigate how closed and open kinetic chain exercises differed in their impact on bone mineral density (BMD) and fall risk in postmenopausal women with osteoporosis. [Subjects and Methods] The research sample consisted of 40 postmenopausal women with osteoporosis with ages between 51 and 58 years old. They were divided at random into two groups of 20 each, respectively receiving closed and open kinetic chain exercises. These exercises were administered three times per week over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…47 The findings of this study are consistent with previous studies that found that exercises improved BMD and decrease fall risk in women with OP. 15 In addition, the current study found that the group of HILT had a better quality of life in comparing with the exercises group, as demonstrated by higher scores in all five EHP-5 domains and a significant difference in the quality-of-life scores mean value, which is consistent with previous research. 48…”
Section: The Pemf Effectssupporting
confidence: 91%
See 2 more Smart Citations
“…47 The findings of this study are consistent with previous studies that found that exercises improved BMD and decrease fall risk in women with OP. 15 In addition, the current study found that the group of HILT had a better quality of life in comparing with the exercises group, as demonstrated by higher scores in all five EHP-5 domains and a significant difference in the quality-of-life scores mean value, which is consistent with previous research. 48…”
Section: The Pemf Effectssupporting
confidence: 91%
“…PEMF exposure affected the formation of growth factors, enhancing the formation of extra-cellular matrix proteins and enhancing tissue repair. 15 Physical therapy has gained more attention in recent years, in addition to pharmacotherapy, for this type of disease. 33 PEMF has been shown to have potential effect in the treatment of OP 21,34 as an effective physiotherapy for various disorders of bone.…”
Section: The Pemf Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few published randomized controlled trials were carried out in Egypt to address the impact of different exercise protocol exercise on the bone mineral density. The study carried out by Thabet et al [54] to investigate how closed and open kinetic chain exercises differed in their impact on bone mineral density (BMD) and fall risk in postmenopausal women with osteoporosis, results revealed that the strongest impact on BMD and fall risk was recorded by the closed kinetic chain exercise. Another study was carried out by Mowafy et al [55] to evaluate the efficacy of the treadmill weight-bearing exercises on BMD and t score mean in cases of osteoporosis El Miedany et al Egyptian Rheumatology and Rehabilitation (2023) 50:7 in breast cancer patients receiving chemotherapy.…”
Section: Rehabilitation Managementmentioning
confidence: 99%
“…Physical activity to maintain bone mass and strength is important for fracture prevention. Many studies have shown that physical activity has a positive effect on femoral bone mineral density (BMD) [ [4] , [5] , [6] ]. However, to perform physical activity, the locomotive system, including muscles, joints, cartilage, bones, the spine, intervertebral discs, and nerves, need to function properly.…”
Section: Introductionmentioning
confidence: 99%